The Influence of Intensive Training in Decoding Skills on Field Dependence-Independence in First Grade Children - R. Allan Dermott; Dodd E. Roberts; Walter G. McIntire (Journal of Research in Rural Education, 1982)
This paper describes the results of a study assessing the impact on field independence-dependence of decoding as a component of reading instruction for 225 first graders.Such drill appears to affect the ability to disembed,a component of field independence-dependence,but not to affect the ability to identify verticality.